New coordination for research in SADCC countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The Southern Africa Centre for the Coordination of Agricultural Research (SACCAR) has been set up in Sebele, Botswana, to oversee cooperation and coordination in research among the nine countries of the Southern African Development Coordination...